Epidemiology of a National Reference Cardiovascular Intensive Care Unit - Miranda, David (2020)
Background: Cardiovascular intensive care units have evolved in time, from being exclusively dedicated to the care of myocardial infarction patients, to treating complex and varied cardiovascular pathologies. We do not have data about the characteristics of patients in cardiovascular intensive careunits in Peru. Material and Methods: We prospectively evaluated the clinical and epidemiological characteristics of patients admitted between July and November 2018 to the intensive and intermediate care unit of the National Cardiovascular Institute INCOR in Lima, Peru. Results: A total of 199 patients were enrolled in the study. The median age was 67 years, 20% older than 80 years and 75.8% males. 60% of cases they came from the emergency unit. The most frequent admissions diagnoses were acute coronary syndromes (ACS) (35%) and acutely decompensated heart failure (20%). In-hospital mortality was 4.5%, higher (12%) in patients with readmissions to intensive care. Conclusions: In this first registry of cardiac critical care in Peru, ACS continues to be the main cause of admission followed by acutely decompensated heart failure. The in-hospital mortality was higher in patients with readmissions to the intensive care unit.